Detection of submucosal gastric fundal varices with multi-detector row CT angiography. Issue 6 (1st June 2003) - Willmann, J K; Weishaupt, D; Böhm, T; Pfammatter, T; Seifert, B; Marincek, B; Bauerfeind, P
Abstract : Background and aim: The diagnosis of submucosal fundal varices is challenging. Currently, endoscopy and endoscopic ultrasound (EUS) are considered most useful for this purpose. The aim of this study was to evaluate if multi-detector row CT (MDCT) angiography contributes to the diagnosis of submucosal fundal varices. Patients and methods: Twenty two patients with endoscopically suspected fundal varices were prospectively included in the study. All patients underwent EUS and MDCT angiography. Levels of agreement between EUS and MDCT angiography for the detection of submucosal and perigastric fundal varices were evaluated by three blinded independent readers. In addition, variceal size and location, as well as afferent and efferent vessels of the submucosal varices, were determined. Results: Good or excellent image quality of MDCT angiography was obtained in 21/22 patients (95%). Based on EUS, submucosal varices were detected in 16 of 22 patients (73%) and perigastric varices in 22/22 patients (100%). Using MDCT angiography, the presence of submucosal varices was confirmed in all of these 16 patients by all three readers. Perigastric varices were also confirmed in all 22 patients by all three readers. In addition, all three readers noted the presence of a submucosal varix in an additional patient which was not detected on initial EUS. MDCT angiography showed an excellent interobserver reliability with regard to variceal diameter (κ=0.90) and variceal location (κ=0.94). Based on MDCT angiography, afferent and efferent vessels of submucosal varices included the left gastric vein in 11 (65%), the posterior/short gastric veins in 15 (88%), gastrorenal shunts in 10 (59%), the left inferior phrenic vein in six (35%), and the left pericardiophrenic vein in six (35%) of 17 patients. Conclusions: MDCT angiography is equivalent to EUS in terms of detection and characterisation of fundal varices, in particular with regard to the distinction between submucosal and perigastric fundal varices.